Six-month bracket failure rate with a flowable composite: A split-mouth randomized controlled trial - Sindhuja Krishnan; Saravana Pandian; R. Rajagopal
ABSTRACT INTRODUCTION: The use of flowable composites as an orthodontic bonding adhesive merits great attention because of their adequate bond strength, ease of clinical handling and reduced number of steps in bonding. OBJECTIVE: The aim of this Randomized Controlled Trial was to comparatively evaluate over a 6-month period the bond failure rate of a flowable composite (Heliosit Orthodontic, Ivoclar Vivadent AG, Schaan) and a conventional orthodontic bonding adhesive (Transbond XT, 3M Unitek). METHODS: 53 consecutive patients (23 males and 30 females) who fulfilled the inclusion and exclusion criteria were included in the study. A total of 891 brackets were analyzed, where 444 brackets were bonded using Heliosit Orthodontic and 447 brackets were bonded using Transbond XT. The survival rates of brackets were estimated with the Kaplan-Meier analysis. Bracket survival distributions for bonding adhesives, tooth location and dental arch were compared with the log-rank test. RESULTS: The failure rates of the Transbond XT and the Heliosit Orthodontic groups were 8.1% and 6% respectively. No significant differences in the survival rates were observed between them (p= 0.242). There was no statistically significant difference in the bond failure rates when the clinical performance of the maxillary versus the mandibular arches and the anterior versus the posterior segments were compared. CONCLUSIONS: Both systems had clinically acceptable bond failure rates and are adequate for orthodontic bonding needs.